The Regulatory Framework for Renewable Energy Sources - Pérez, Antonio Vázquez; Castillo, Guillermo Antonio Loor; Alava, Lenin Agustin Cuenca; Chilan, Julio Cesar Hernández (International Research Journal of Management, IT & Social Sciences, 2016)
This work offers an analytical view about the problems related to electricity generation using fossil fuels and the role renewable energy can played, especially solar photovoltaic and wind energy applied to distributed generation, diversification. An analysis about the historical development of the regulatory framework posed in a group of countries. Also an analysis of the main consequences associated with the deregulation of the Ecuadorian market linked to renewable sources is presented. Photovoltaic energy is mainly considered, as well as an insight on the importance of implementing an appropriate regulatory system, and support measures which regulate new ways of generation and supply of energy. The main concern is mostly related to the incorporation of independent producers as a new pattern in the system of power generation in the country. New concepts are considered for drawing supportive measures and specific regulations related to RES as well as the competence of a group of specific regulations which aim at regulating the payment of the electricity generated by independent producers. Chromatic scale maps are shown on the study of solar and wind, which can be used to make the feasibility studies prior to the introduction of technologies that allow us to use these sources.